Biology, harmfulness and improvement of control measures against cabbage stem flea beetle, Psylliodes chrysocephalus Linnaeus, 1758 (Coleoptera: Chrysomelidae) - Bekzat Mombayeva; Nagima Tumenbayeva; Gulnara Akhauova; Assel Karabayeva; Аyagoz Mendigaliyeva; Roza Bakessova; Gaukartas Abysheva; Gulzat Yessenbekova (Caspian Journal of Environmental Sciences)
Psylliodes chrysocephalus L., a significant pest affecting cruciferous crops, causes substantial agricultural damage due to its biological and ecological traits. This study investigates the species' life cycle, host preferences, and environmental adaptability, revealing that adults and larvae preferentially target young plants, reducing crop vigor and yield losses of up to 20% in some regions. The pest's rapid reproductive rate—capable of laying up to 1000 eggs per female—and resistance to conventional insecticides exacerbate its economic impact. Current control strategies rely heavily on synthetic pesticides but are increasingly ineffective and pose risks to non-target organisms. To address these challenges, integrated pest management (IPM) approaches were evaluated, combining biological control agents (e.g., entomopathogenic fungi) with cultural practices like crop rotation and selective insect growth regulators. Field trials demonstrated that IPM strategies reduce pest populations by up to 60% while minimizing environmental harm. Additionally, genomic insights into P. chrysocephalus detoxification mechanisms inform the development of targeted insecticides capable of overcoming existing resistances.